Relasi Nasionalisme dan Islam dalam Lirik Syair Ya Lal Wathan - Abdur Rosid (Jurnal Indonesia Sosial Teknologi, 2022)
The values ​​of nationalism and religion contained in the lyrics of the march of Syubbanul wathan or commonly called Ya Lal Wathan with the title "Relation of Nationalism and Islam in the lyrics of Mars Syubbanul wathan (Ibn Khaldun's Ashabiyah perspective)". This study aims to describe events that occurred in the past. Meanwhile, the theoretical basis used in this study is using the Ashabiyah theory according to Ibn Khaldun about a sense of solidarity and unity which is the capital of the formation of the State. Based on the results of the research that: 1) the lyrics of the march of Syubbanul wathan contain the value of nationalism which is in accordance with Islamic teachings about love for the homeland. 2) Nationalism and Islam are the two main components in the history of the founding of the State of Indonesia as the freedom fighters stated in several writings including Mars Ya Lal Wathan. And both must be preserved in order to maintain the stability of the sustainability of the life of the nation and state. As the Ashabiyah theory about the cycle of growth and development of the State